An Extra Cue Is Beneficial for Native Speakers but Can Be Disruptive for Second Language Learners: Integration of Prosody and Visual Context in Syntactic Ambiguity Resolution - Nakamura, Chie; Arai, Manabu; Hirose, Yuki; Flynn, Suzanne (Frontiers in Psychology, 2020)
It has long been debated whether non-native speakers can process sentences in the same way as native speakers do or they suffer from certain qualitative deficit in their ability of language comprehension. The current study examined the influence of prosodic and visual information in processing sentences with a temporarily ambiguous prepositional phrase ("Put the cake on the plate in the basket") with native English speakers and Japanese learners of English. Specifically, we investigated (1) whether native speakers assign different pragmatic functions to the same prosodic cues used in different contexts and (2) whether L2 learners can reach the correct analysis by integrating prosodic cues with syntax with reference to the visually presented contextual information. The results from native speakers showed that contrastive accent was interpreted as contrastive when contrast was present in visual scenes but not when it was not, which supports the view that the pragmatic functions of intonation categories are highly context dependent. The results from L2 learners showed that visually presented context alone helped L2 learners to reach the correct analysis. However, L2 learners were unable to assign contrastive meaning to the prosodic cues when there were two potential referents in the visual scene. The results suggest that L2 learners are not capable of integrating multiple sources of information in an interactive manner during real-time language comprehension.